TECHNOLOGICAL ASPECT OF IDENTIFYING AND OVERCOMING THE CAUSES OF STUDENT FAILURE AND TAKING INTO ACCOUNT THE INDIVIDUAL APPROACH IN LEARNING - Reva, Yu.V. (Pedagogy of Higher and Secondary Education, 2009)
The article presents the technological aspect of finding and salving the reasons of pupils unsuccessfulness and taking into consideration the individual approach in teaching.